2021
DOI: 10.1038/s41398-020-01146-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic differences between bipolar disorder type 1 and 2 in multiplex families

Abstract: The two major subtypes of bipolar disorder (BD), BD-I and BD-II, are distinguished based on the presence of manic or hypomanic episodes. Historically, BD-II was perceived as a less severe form of BD-I. Recent research has challenged this concept of a severity continuum. Studies in large samples of unrelated patients have described clinical and genetic differences between the subtypes. Besides an increased schizophrenia polygenic risk load in BD-I, these studies also observed an increased depression risk load i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
(82 reference statements)
1
16
0
Order By: Relevance
“…The bipolar spectrum includes 7 of the 37 patients with bipolar disorder had committed suicide, a number close to known prevalence of death by suicide in BD. Suicide mainly occurs during the depressive state of the disease and – occasionally-during a manic episode and could be connected to certain patterns of gene expression [61], biomarker differences [63] and vary during an acute or prolonged depressive or manic or mixed episode) [64], including the cerebellum. Finally, the genetic characteristics of post-mortem brain tissue sampling could be divergent from the same characteristics of the living brain, in health and disease; still they remain one of the cornerstones of research on the neurobiology of the CNS and its disorders [65], [66], [67] [68].…”
Section: Discussionmentioning
confidence: 99%
“…The bipolar spectrum includes 7 of the 37 patients with bipolar disorder had committed suicide, a number close to known prevalence of death by suicide in BD. Suicide mainly occurs during the depressive state of the disease and – occasionally-during a manic episode and could be connected to certain patterns of gene expression [61], biomarker differences [63] and vary during an acute or prolonged depressive or manic or mixed episode) [64], including the cerebellum. Finally, the genetic characteristics of post-mortem brain tissue sampling could be divergent from the same characteristics of the living brain, in health and disease; still they remain one of the cornerstones of research on the neurobiology of the CNS and its disorders [65], [66], [67] [68].…”
Section: Discussionmentioning
confidence: 99%
“… 53 Second, a comparison of bipolar disorder types 1 and 2 showed that these two groups do not have a similar profile of polygenic risk, at least regarding the risk of depression. 54 Third, bipolar disorder PRS are associated not only with other psychiatric phenotypes, but also with several clinical features and potential biomarkers in different psychiatric conditions. 55 Finally, certain clinically relevant features in bipolar disorder, such as response to lithium treatment or age at onset, are not associated with bipolar disorder PRS but are associated with other psychiatric PRS.…”
Section: Polygenicity and Polygenic Scoresmentioning
confidence: 99%
“…Many of the samples studied include individuals with a broad range of bipolar spectrum disorders, and analyses did not differentiate those with bipolar I from those with bipolar II or cyclothymic disorders. Given increasing evidence for genetic differentiation in the forms of disorder [ 81 ], examining effects within subtypes will be an important goal for future research. It is also the case that most studies were only statistically powered to examine change in the level of manic symptoms, and not the onset or recurrence of disorder.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%